Investigating the prevalence of contact dermatitis and its related factors among hospital staff during the outbreak of the COVID-19 epidemic: A cross-sectional study - Masoomeh Abdi; Bita Falahi; Farzad Ebrahimzadeh; Kiomars Karami-zadeh; Lida Lakzadeh; Zahra Rezaei-nasab (Wolters Kluwer Medknow Publications, 2022)
Background: Frequent hand washing and prolonged mask use during the Coronavirus disease (COVID-19) pandemic may cause contact dermatitis in hospital staffs. This study was conducted to investigate the prevalence of contact dermatitis and its related factors among hospital staff during the COVID-19 pandemic. Materials and Methods: The present cross-sectional study was conducted among the hospital personnel of Aligoudarz Shahid Valian Hospital, Lorestan, Iran, from March to June 2020. Sampling was performed using the complete enumeration method and 142 hospital staff (physicians, nurses, service personnel, nurses' aides, secretaries, and laboratory and radiology experts) participated in the study. Data were collected using a 3-part questionnaire containing a demographic characteristics form, job information form, and the Nordic Occupational Skin Questionnaire (NOSQ). The obtained data were analyzed using descriptive statistics, Chi-square, and Spearman's correlation coefficient in SPSS. Results: The prevalence of hand dermatitis in participants was 88.02%, and facial dermatitis with the surgical mask was 71.83% and with n95 mask was 81.69%. The most-reported symptom was dryness of the hand. The most common symptom observed after prolonged use of surgical (55 Samples; 38.73%) and n95 masks (79 Samples; 55.63%) was redness. The frequency of hand washing (F = 8; p = 0.017) and the use of liquid soap (F = 4; p = 0.047) had a significant interrelation with the severity of dermatitis. Conclusions: Planning for preventive actions and management of the current situation should be a priority among the policies of hospital managers given the high prevalence of hand and face dermatitis among hospital staff.